Detecting Changes in Vegetation Trends in the Middle East and North Africa (MENA) Region Using SPOT Vegetation - Ghaleb Faour; Mario Mhawej; Abbas Fayad (Cybergeo, 2016)
The Middle East and North Africa (MENA) can be considered as the most water-scarce regions of the world and thus affecting the status of vegetation in this zone. Normalized Difference Vegetation Index (NDVI) datasets are used worldwide for large-area mapping and monitoring. Time series analysis techniques are used to define, evaluate, and monitor vegetation dynamics and variability using up-to-date remote sensing datasets. This study assesses vegetation degradation in the Arab countries using the SPOT Vegetation derived NDVI time series data of remotely sensed imageries for the time period between 1999 and 2012. Five classes were identified: Hot spot, negative change, no change, positive change and bright spot areas. Results indicate a severe decrease in the vegetation cover in almost 553 000 km2 of the total Arab region surface. On the other hand, only less than 1% of the region witnessed positive ‎changes in the vegetation cover. The positive and bright spot areas are mainly located in Algeria and Egypt, as well as in the southern part of Somalia and Iraq. Negative change and hot spot areas were found to be wide spreading all over the Arab countries, irrespective of the location, climate and topography. In addition, it is found that the vegetation changes in these regions are mainly related to human activities and decisions; climate change plays only a secondary role in the MENA region.